Evaluating Inpatient Hospital Charges Associated With Trauma Service Patients Participating in an Accountable Care Organization - Richard J Salhany; Daniel Genovese-Scullin; Jasmin A Eversley-Danso; Humroy Mendez; Vladimir Rubinshteyn; Nisha Lakhi (SAGE Publishing, 2023)
Background: The Medicare Accountable Care Organization (ACO) Program has created a vehicle for providers who practice cost containment and exceed quality for the Medicare population. The success of ACO's nationwide have been well documented. However, there is little research evaluating if there is a cost saving benefit in trauma care with respect to participating in an ACO. Thus, the primary objective of this study was to evaluate inpatient hospital charges associated with trauma service utilization of patients participating in the ACO compared to non-ACO patients. Methods: This case-control retrospective study includes a comparison of inpatients charges of ACO patients (cases) and general trauma patients (controls) presenting to our trauma center in Staten Island, New York from January 1st, 2019 to December 31st, 2021. A 1:1 matching of case to control was performed based on age, sex, race, and injury severity score. Statistical analysis was performed with IBM SPSS, with P  < .05 as significant. Results: A total of 80 patients were included in the ACO cohort and 80 matched in the General Trauma cohort. Patient demographics were similar. Comorbidities were similar with the exception of a higher in incidence of hypertension (75.0% vs 47.5%, P  < .001) and cardiac disease (35.0% vs 17.5%, P  = .012) in the ACO cohort. Both the ACO and general trauma cohort had similar Injury Severity Scores, number of visits and lenght of stay. Both charge total ($76 148.93 vs $70 916.82, P  = .630) receipt total ($15 080.26 vs $14 180, P  = .662) charges were similar between ACO and General Trauma patients. Conclusion: In spite of increased incidence of hypertension and cardiac disease in ACO trauma patients, mean Injury Severity Score, number of visits, length of hospital stay, ICU admission rate and charge total was similar compared to general trauma patients presenting to our Level 1 Adult Trauma Center.